Body Composition of National Collegiate Athletic Association (NCAA) Division I Female Soccer Athletes through Competitive Seasons - Roelofs, Erica; Bockin, April; Bosch, Tyler; Oliver, Jonathan; Bach, Christopher W.; Carbuhn, Aaron; Stanforth, Philip R.; Dengel, Donald R. (International Journal of Sports Medicine, 2020)
The purpose of this study was to examine body composition of National Collegiate Athletic Association Division I female soccer players by position and season. One hundred seventy-five female athletes were categorized by positions of forward (n=47), midfielder (n=51), defender (n=57), and goalkeeper (n=20). A dual X-ray absorptiometry scan assessed percent body fat, total lean mass, total fat mass, arm and leg lean mass and fat mass, and visceral adipose tissue. Goalkeepers had significantly higher total, arm, and leg lean mass and fat mass compared to all other positions (p<0.05). For seasonal changes, body fat percentage was significantly higher in winter off-season (26.7%) compared to summer off-season (25.7%) and pre-season (25.8%; p<0.01) for all positions. Total and leg lean mass was significantly lower in winter off-season compared to all other seasons, and total lean mass was significantly higher in summer off-season than pre-season (p<0.01). Overall, goalkeepers were significantly different than all other positions. Body fat percentage increased and lean mass decreased in winter off-season indicating potential undesired changes in training and/or nutrition over the break whereas lean mass was the highest in summer off-season potentially reflecting the emphasis on resistance training and increased volume of training.
Keywords: dual x-ray absorptiometry; lean mass; visceral adipose tissue; sports